2014
DOI: 10.1039/c3ra47788f
|View full text |Cite
|
Sign up to set email alerts
|

Adventures in corrole features by electrospray ionization mass spectrometry studies

Abstract: In this short review the importance of electrospray mass spectrometry in corrole chemistry is highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 134 publications
(161 reference statements)
0
7
0
Order By: Relevance
“…A similar procedure was used to prepare the Zn­(II) complex of meso -triphenylcorrole . The complexation of H 3 TPFC with several divalent transition-metal ions, including Zn 2+ , was studied by liquid secondary ion and electrospray mass spectrometry. , …”
Section: Functionalization At the Inner Core Positionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar procedure was used to prepare the Zn­(II) complex of meso -triphenylcorrole . The complexation of H 3 TPFC with several divalent transition-metal ions, including Zn 2+ , was studied by liquid secondary ion and electrospray mass spectrometry. , …”
Section: Functionalization At the Inner Core Positionsmentioning
confidence: 99%
“…185 The complexation of H 3 TPFC with several divalent transition-metal ions, including Zn 2+ , was studied by liquid secondary ion and electrospray mass spectrometry. 186,187 N-Alkyl corroles are easily metalated with zinc(II) acetate in pyridine to yield zinc(II) corrole complexes such as the Zn(II)(N(21)-benzyl-TPFC) (py) (52) and Zn(II)(N(21)picolyl-TPFC) (53) (Figure 12). 144,188 Metalation of the triply linked 2H-corrole dimers (with two inner NH groups in each corrole unit) 54a and 54b with Zn(OAc) 2 •2H 2 O in CHCl 3 at reflux for 20 h gave the bis(zinc(II)) complexes Zn54a and Zn54b in 76% and 79% yield, respectively (Scheme 10).…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Also, according to SciFinder, more than 70 reviews on selected aspects of corroles have been published over the last 2 decades, although most of these publications would more accurately be classified as minireviews on very narrowly focused aspects of corrole chemistry or properties. Some of the above SciFinder-listed reviews on corroles have included discussions of the compound’s redox reactivity, but none has been devoted exclusively to the electrochemical properties of corroles as a function of changes in the central metal ion, compound structure, or solution conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to monitor the reaction by ESI or MALDI mass spectrometry using the negative mode detection. Two reviews reported the best matrix and conditions to use when running MALDI/ TOF 279 or ESI 280 mass spectra for small molecules or corrole derivatives. Very interestingly, the UV-visible spectra of the isolated tetra-thiocyanatocorroles show, in acetonitrile, the presence of four Q-bands, quite similar to the Q-type bands of chlorophyll-a.…”
Section: Photodynamic Therapy (Pdt) Applicationsmentioning
confidence: 99%